2008
DOI: 10.1021/la8025792
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects in the Reaction of Aryl Radicals on Surfaces

Abstract: Steric effects are investigated in the reaction of aryl radicals with surfaces. The electrochemical reduction of 2-, 3-, 4-methyl, 2-methoxy, 2-ethyl, 2,6-, 2,4-, and 3,5-dimethyl, 4-tert-butyl, 3,5-bis-tert-butyl benzenediazonium, 3,5-bis(trifluoromethyl), and pentafluoro benzenediazonium tetrafluoroborates is examined in acetonitrile solutions. It leads to the formation of grafted layers only if the steric hindrance at the 2- or 2,6-position(s) is small. When the 3,5-positions are crowded with tert-butyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 40 publications
9
150
0
Order By: Relevance
“…[137] [138] Furthermore a diazonium cation can also attack an aryl radical already attached to the surface (c in Scheme 6). The radical forming electroreduction occurs preferentially at freely available electrode surfaces quickly covering remaining uncoated surface areas.…”
Section: Surface Functionalization By Electrochemical Reduction Of DImentioning
confidence: 99%
See 4 more Smart Citations
“…[137] [138] Furthermore a diazonium cation can also attack an aryl radical already attached to the surface (c in Scheme 6). The radical forming electroreduction occurs preferentially at freely available electrode surfaces quickly covering remaining uncoated surface areas.…”
Section: Surface Functionalization By Electrochemical Reduction Of DImentioning
confidence: 99%
“…With appropriate experimental conditions homogenous monolayers can be grafted, which is rather difficult to achieve by traditional chemical methods only. [20][139]- [141] Recently, Pinson [137] studied the steric effects in the reaction of aryl radicals on surfaces. They have shown that it is possible to prevent multilayer formation by hindering different positions of the diazonium ions.…”
Section: Surface Functionalization By Electrochemical Reduction Of DImentioning
confidence: 99%
See 3 more Smart Citations